The effect of different oxygen exchange layers on TaOx based RRAM devices. (12th December 2017) - Alamgir, Zahiruddin; Holt, Joshua; Beckmann, Karsten; Cady, Nathaniel C
Abstract: In this work, we investigated the effect of the oxygen exchange layer (OEL) on the resistive switching properties of TaO x based memory cells. It was found that the forming voltage, SET-RESET voltage, R off, R on and retention properties are strongly correlated with the oxygen scavenging ability of the OEL, and the resulting oxygen vacancy formation ability of this layer. Higher forming voltage was observed for OELs having lower electronegativity/lower Gibbs free energy for oxide formation, and devices fabricated with these OELs exhibited an increased memory window, when using similar SET-RESET voltage range.